Association between 5q23.2-located polymorphism of CTXN3 gene (Cortexin 3) and schizophrenia in European-Caucasian males; implications for the aetiology of schizophrenia - Šerý, Omar; Lochman, Jan; Povová, Jana; Janout, Vladimír; Plesník, Jiří; Balcar, Vladimir J (Behavioral and brain functions, 2015)
BACKGROUND: The objective of the study was to examine several polymorphisms in DISC1 and CTNX3 genes as possible risk factors in schizophrenia. DISC1 (disrupted-in-schizophrenia 1) has been studied extensively in relation to mental disease while CTXN3, has only recently emerged as a potential "candidate" gene in schizophrenia. CTXN3 resides in a genomic region (5q21-34) known to be associated with schizophrenia and encodes a protein cortexin 3 which is highly enriched in brain. METHODS: We used ethnically homogeneous samples of 175 male patients and 184 male control subjects. All patients were interviewed by two similarly qualified psychiatrists. Controls were interviewed by one of the authors (O.S.). Genotyping was performed, following amplification by polymerase chain reaction (PCR), using fragment analysis in a standard commercial setting (Applied Biosystems, USA). RESULTS: We have found a statistically significant association between rs6595788 polymorphism of CTXN3 gene and the risk of schizophrenia; the presence of AG genotype increased the risk 1.5-fold. Polymorphisms in DISC1 gene showed only marginally statistically significant association with schizophrenia (rs17817356) or no association whatsoever (rs821597 and rs980989) while two polymorphisms (rs9661837 and rs3737597) were found to be only slightly polymorphic in the samples. CONCLUSION: Evidence available in the literature suggests that altered expression of cortexin 3, either alone, or in parallel with changes in DISC1, could subtly perturb GABAergic neurotransmission and/or metabolism of amyloid precursor protein (APP) in developing brain, thus potentially exposing the affected individual to an increased risk of schizophrenia later in life.
Keywords: genetické asociační studie; alely; Alleles; Nerve Tissue Proteins; schizofrenie; Adult; Male; Schizophrenia; lidé; Genotype; lidé středního věku; Humans; běloši; Polymorphism, Single Nucleotide; Middle Aged; Gene Frequency; frekvence genu; jednonukleotidový polymorfismus; White People; DNA; proteiny nervové tkáně; mužské pohlaví; rizikové faktory; Risk Assessment; dospělí; Genetic Association Studies; hodnocení rizik; Membrane Proteins; membránové proteiny; genotyp; Risk Factors